150 Estimation of an MCID for AIMS Total Score Change in Tardive Dyskinesia. (15th June 2018) - Sajatovic, Martha; Cutler, Andrew J.; Farahmand, Khodayar; Burke, Joshua; Siegert, Scott; Liang, Grace S.
Abstract: Background: The efficacy of valbenazine (INGREZZA) in tardive dyskinesia (TD) was demonstrated in placebo-controlled clinical trials, based on the Abnormal Involuntary Movement Scale (AIMS) total score (sum of items 1-7). In these trials, mean changes in the AIMS total score were significantly greater with valbenazine 80 mg than with placebo. Currently, no minimal clinically important difference (MCID) has been established for the AIMS total score in patients with TD. Using valbenazine trial data, analyses were conducted to establish a MCID for AIMS total score in TD. Methods: Data were pooled from three 6-week trials: KINECT (NCT01688037), KINECT 2 (NCT01733121), KINECT 3 (NCT02274558). Using the Clinical Global Impression ofChange (CGI-TD) as an anchor comparison, AIMS total score changes from baseline to Week 6 were summarized for all study participants (pooled valbenazine and placebo groups) with a "minimal" CGI-TD score of ≤3 (minimally improved or better) or "robust" ≤2 (much improved or better) at Week 6. Results: In the pooled population (N=373), 72% and 29% of all participants had CGI-TD scores of ≤3 and ≤2, respectively. The median (maximum, minimum) change from baseline in AIMS total score at Week 6 was -2 (-13, 8) in participants with CGI-TD score ≤3 and -3 ( 13, 8) in participants with a score ≤2. Conclusion: Pooled data from 3 randomized, double-blind, placebo-controlled trials suggest that a 2 point decrease in AIMS total score may represent the minimal clinically meaningful improvement. Larger AIMS score improvements were associated with "much improved" or "very much improved" CGI TD assessments. Funding Acknowledgements: This study was funded by Neurocrine Biosciences, Inc.